2019
DOI: 10.1111/hepr.13293
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection for recurrent hepatocellular carcinoma after radiofrequency ablation therapy

Abstract: Aim: Although radiofrequency ablation (RFA) is an effective local treatment of hepatocellular carcinoma (HCC), local recurrence is relatively frequent. We aimed to elucidate the validity of salvage liver resection for recurrent HCC after RFA.Methods: Patients who underwent liver resection for recurrent HCC after RFA (LR after RFA) and those who underwent second liver resection for recurrent HCC (second LR) were included. The short-term outcomes were compared between the two groups. The survival rates between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…However, evidence from clinical practice has indicated that BCLC A patients failing local ablation could be effectively treated with LR prior to adopting rescue chemoembolization. (39) Another example of evidence-based right-to-left sequential migration is downstaging, in which locoregional therapies would allow the reinclusion of those patients in the LT criteria who were initially considered not transplantable. (3) The evidence of the success of right-to-left treatment stage migration is probably the main reason prompting the necessity to interpret the BCLC algorithm with flexibility, as recognized by the latest EASL and AASLD guidelines as well.…”
Section: Applications Of Treatment Stage Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence from clinical practice has indicated that BCLC A patients failing local ablation could be effectively treated with LR prior to adopting rescue chemoembolization. (39) Another example of evidence-based right-to-left sequential migration is downstaging, in which locoregional therapies would allow the reinclusion of those patients in the LT criteria who were initially considered not transplantable. (3) The evidence of the success of right-to-left treatment stage migration is probably the main reason prompting the necessity to interpret the BCLC algorithm with flexibility, as recognized by the latest EASL and AASLD guidelines as well.…”
Section: Applications Of Treatment Stage Migrationmentioning
confidence: 99%
“…However, evidence from clinical practice has indicated that BCLC A patients failing local ablation could be effectively treated with LR prior to adopting rescue chemoembolization. ( 39 ) Another example of evidence‐based right‐to‐left sequential migration is downstaging, in which locoregional therapies would allow the reinclusion of those patients in the LT criteria who were initially considered not transplantable. ( 3 )…”
Section: Treatment Stage Migrationmentioning
confidence: 99%
“…The diameter and number of primary HCC were not significantly related to HCC re-recurrences in this study. Although some studies have demonstrated that the diameter and number of primary HCC had no significant association with the prognosis after initial recurrence, some researchers have reported a significant correlation between the tumor size and survival [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…A P-value of less than 0.10 was set as the cut-off value for elimination. The following 18 variables, considered as potential confounders, were examined: age (≥ 70 versus < 70 years), sex, positive for hepatitis B or C virus, alcohol abuse, diabetes mellitus, platelet count (≥ 15 × 10 4 versus < 15 × 10 4 /mL), serotonin (≥ 90.5 versus < 90.5 ng/mL), Child-Pugh score (5 vs ≥ 6), indocyanine green clearance rate at 15 minutes (ICGR15) (≥ 15 versus < 15%), esophageal varices, serum alpha-fetoprotein level (≥ 100 versus < 100 ng/mL), serum DCP level (≥ 100 versus < 100 mAU/mL), tumor size (≥ 3.0 versus < 3.0 cm), tumor number (single versus multiple), poorly differentiated, tumor thrombus, and liver cirrhosis [21,22]. Statistical signi cance was set at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%